Development of novel molecular tools to study the dynamics of individual SAR11 phylotypes in microbial communities - Poorna, Weerarathna Vidanage (Nanyang Technological University, 2023)
Marine and freshwater systems cover more than 70% of the earth surface and harbour more than 99% of the biosphere. SAR11 is considered the most abundant planktonic bacterial group in the oligotrophic ecosystems, representing approximately 25% of planktonic bacterial cells. It consists of subgroups (ecotypes) that occupy different ecological niches and vary in metabolic potentials. Being able to detect different ecotypes would allow researchers to gain a better understanding of nutrient cycling in aquatic systems; yet it is challenging to differentiate the closely related phylotypes of the SAR11 group using conventional molecular methods. This thesis describes a methodology to develop a molecular tool (including qPCR primers) to detect SAR11 phylotypes at higher taxonomic resolution based on bioinformatic analysis of the genomes of SAR11. Following in-silico validation of the sequencing data and designed qPCR primers, a freshwater SAR11 (LD12) was identified in the Singapore Quarry lake system. The SAR11 bacterial group is also known to play an important role in global biogeochemical cycles. Hence a further aim was to shed light on the biogeochemical role of LD12 bacteria in tropical freshwater systems, as exemplified by the freshwater quarry lake system. Interactions between LD12 bacteria and other community members based on cooccurrence patterns were used to suggest putative metabolic interactions between LD12 and other selected members of the microbial community. The developed marker genes can be applied to monitor SAR11 members in a natural or engineered system. Limitations of current techniques used to develop the molecular tools and future developments are also discussed.